Lateral Structural Variation of the Lithosphere‐Asthenosphere System in the Northeastern to Eastern Iranian Plateau and Its Tectonic Implications. Issue 1 (19th January 2021) - Wu, Zimu; Chen, Ling; Talebian, Morteza; Wang, Xu; Jiang, Mingming; Ai, Yinshuang; Lan, Haiqiang; Gao, Yifan; Khatib, Mohammad Mahdi; Hou, Guangbing; Chung, Sun‐Lin; Liang, Xiaofeng; et al.
Abstract: The Iranian plateau is a natural laboratory for deciphering the lithospheric deformation and deep dynamics in response to the Neo‐Tethyan subduction and subsequent Arabia‐Eurasia continental collision. Here we used S‐wave receiver function data from a dense seismic array to construct the structural image of the lithosphere‐asthenosphere system across the northeastern to eastern Iranian plateau. The lithosphere‐asthenosphere boundary (LAB) is consistently imaged, being relatively flat at 80–90 km depth in eastern Iran, but deepening northward to ∼120 km depth beneath the Kopeh Dagh‐Turan platform boundary with an overall "root‐like" shape in northeastern Iran. A shallower (<45 km) and a deeper Moho (∼50–55 km) are also observed beneath eastern and northeastern Iran, respectively, suggesting similar crustal deformation to mantle lithosphere but different patterns laterally. Moreover, a strong positive velocity discontinuity (PVD) is detected at ∼170 km depth beneath eastern Iran, possibly representing the base of an asthenospheric low‐velocity layer (LVL). Waveform modeling reveals large velocity contrasts of ∼4%–6% over a depth range of less than 30 and 20 km, respectively, across the LAB and the asthenospheric PVD. Combining our new results with geological and petrological constraints, we deduced that the asthenospheric LVL contains a small amount of melt, with sharp boundaries separating from the nearly melt‐free lithosphere above (LAB) and deeper mantle below (PVD). The observed structural variations of the lithosphere‐asthenosphere system across the study region may result from the complex lithospheric deformation in response to the Arabia‐Eurasia collision and effects of multiple tectono‐thermal events associated with the earlier Neo‐Tethyan subduction. Key Points: Lateral variations of the lithospheric and sub‐lithospheric structures are investigated across northeastern to eastern Iran Lithospheric responses to the Arabia‐Eurasia convergence vary across the interior of the Iranian plateau Hydrous melting possibly occurs in the asthenospheric low‐velocity layer beneath eastern Iran